Manajemen Internal Perusahaan Terhadap Financial Distress: Peran Keragaman Gender - Setyani, Aprilia; Djuminah, Djuminah (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to look for empirical evidence regarding earnings management, cash flow and internal control of financial distress with gender diversity as a moderating variable. The population in this research is banking companies registered on the IDX with a sample of 39 banking companies during 2020-2022. In this research, evidence was found that earnings management influences the occurrence of financial distress in companies. Meanwhile, cash flow and internal control do not have a significant influence on the occurrence of financial distress. In addition, gender diversity cannot moderate the relationship between earnings management, cash flow and internal control on financial distress.